Design of a passive CMOS implantable continuous monitoring biosensors transponder front-end. (August 2019) - Shahroury, Fadi R.; Mohammad, Ahamd A.
Abstract: This paper presents the design of an implantable passive transponder front-end that can power implantable biosensors and also provide a power-efficient communication means for it with an extracorporeal reader, enabling continuous real-time monitoring of internal body parameters. The implantable passive transponder front-end is composed of power management circuity, demodulator, oscillator, and load-shift keying modulator. To control and power the implantable biosensors we used a 13.56 MHz Pulse Width Modulated signal. A stable DC voltage, data and clock are extracted from this modulated signal. The proposed transponder was designed, simulated and layout in a 40-nm 1P9M TSMC's CMOS technology. The simulation shows that the proposed implantable passive transponder front-end has a total average power consumption of 17.14 μW, with receiving data rate of 142.85 kB/s and transmitting data rate of 50 kB/s.